EUPATI Guidance for Patient Involvement in Medicines Research and Development (R&D); Guidance for Pharmaceutical Industry-Led Medicines R&D - Warner, Kay; See, Wolf; Haerry, David; Klingmann, Ingrid; Hunter, Amy; May, Matthew (Frontiers in Medicine, 2018)
The importance and merits of greater patient involvement in medicines research and development (R&D) are commonly acknowledged and are thought to offer benefits for all involved parties. It helps to improve discovery, development, and evaluation of new effective medicines, based on the collaborative identification and understanding of unmet needs, research priorities, optimization of clinical study design, outcome measures, and endpoint development. It can result in increased transparency, trust and mutual respect between patients and other stakeholders. This applies to all stages of medicines R&D, from industry-led research, to regulation and licensing of medicines, to appraisal by health technology assessment (HTA) bodies. Integration of patients into the medicines development process needs to be structured and governed by clear rules and modes of operation to be effective and yield the best results for all stakeholders. Existing codes of practice for patient involvement with various stakeholders do not comprehensively cover the full scope of R&D, with the exception of more general statements applicable to interaction. Overarching guidance on meaningful and ethical interaction is missing. One specific aim of the European Patients' Academy on Therapeutic Innovation (EUPATI) was to close this gap through the development of guidance documents for selected stakeholders. Four separate guidance documents were developed, incorporating the results from comprehensive internal and external consultation. They cover patient involvement in: pharmaceutical industry-led medicines R&D; ethics committees; regulatory authorities; HTA. Each guidance suggests where patient involvement could be adopted or strengthened. The EUPATI guidance document for patient involvement in industry-led medicines research and development covers the interaction between patients and the pharmaceutical industry within all functions throughout the medicines R&D lifecycle in relation to medicines for human use. It relates to activities pre-approval and post approval, involving individuals and groups of patients. The guideline distinguishes between the level of expertise in a disease area that is required and the different areas where patient involvement can take place; however, this is not meant to limit involvement, and these opportunities may change and increase over time. This EUPATI guidance document is aimed at the pharmaceutical industry who want to engage patients in R&D activities, however all stakeholders involving patients in pharmaceutical-led medicines R&D should understand and use this EUPATI guidance document.